Fenomen wyborczy Platformy Obywatelskiej - Czech, Beata (My University, 2014)
Celem tej pracy jest próba odpowiedzi dlaczego partia rządząca po raz drugi wygrała wybory. Zarówno rozważania teoretyczne, jak i cześć badawcza, będzie próbą odpowiedzi – na czym polega fenomen Platformy Obywatelskiej, która już 7 rok z rzędu sprawuje w Polsce władzę.

The aim of this work is an attempt to answer why the ruling party for the second time won the elections. Both theoretical considerations and honor research will attempt to answer - what is the phenomenon of the Civic Platform, which is already seven years in a row exercises power in Poland
The phenomenon of electoral Civic Platform
Keywords: the Polish party system after 2005; concept of political marketing; definicja partii politycznych; historia Platformy Obywatelskiej; polski system partyjny po 2005 r.; program wyborczy partii; pojęcie marketingu politycznego; definition of political parties; history of the Civic Platform party's election program